Pelatihan dan Pendampingan Pelaporan Keuangan Badan Usaha Milik Desa (BUMDES) Mekar Jaya Desa Kandangan Temanggung - Hendrawan Santosa Putra; Taufik Kurrohman; Andriana Andriana; Resha Dwi Ayu Pangesti Mulyono (AJAD : Jurnal Pengabdian kepada Masyarakat, 2025)
Community Service Activity is a training and mentoring activity in the preparation of financial reports for Village-Owned Enterprises (BUMDES) as an effort to strengthen the economic capacity of villages and improve transparency at the village level, in this case for BUMDES Mekar Jaya in Kandangan, Temanggung. By introducing Microsoft Excel, participants are introduced to functions that can be used to prepare financial reports so that they are accurate, systematic, and accountable. Training on entering financial data, creating report formats, and using analytical functions to assess BUMDES performance will be given. Mentoring is carried out practically so that participants are able to apply the knowledge they have gained in real financial management activities. This program is expected to assist BUMDES managers in preparing quality financial reports that are transparent and useful for decision-making, contributing to good governance and sustainable economic development at the village level.